Association of the Cytoplasmic Membrane Protein XpsN with the Outer Membrane Protein XpsD in the Type II Protein Secretion Apparatus of Xanthomonas campestris pv. Campestris - Lee, Hsien-Ming (American Society for Microbiology, 2000)
An xps gene cluster composed of 11 open reading frames is required for the type II protein secretion in Xanthomonas campestris pv. campestris. Immediately upstream of the xpsD gene, which encodes an outer membrane protein that serves as the secretion channel by forming multimers, there exists an open reading frame (previously designated ORF2) that could encode a protein of 261 amino acid residues. Its N-terminal hydrophobic region is a likely membrane-anchoring sequence. Antibody raised against this protein could detect in the wild-type strain of X. campestris pv. campestris a protein band with an apparent molecular mass of 36 kDa by Western blotting. Its aberrant slow migration in sodium dodecyl sulfate-polyacrylamide gels might be due to its high proline content. We designated this protein XpsN. By constructing a mutant strain with an in-frame deletion of the chromosomal xpsN gene, we demonstrated that it is required for the secretion of extracellular enzyme by X. campestris pv. campestris. Subcellular fractionation studies indicated that the XpsN protein was tightly associated with the membrane. Sucrose gradient sedimentation followed by immunoblot analysis revealed that it primarily appeared in the cytoplasmic membrane fractions. Immune precipitation experiments indicated that the XpsN protein was coprecipitated with the XpsD protein. In addition, the XpsN protein was co-eluted with the (His)(6)-tagged XpsD protein from the metal affinity chromatography column. All observations suggested that the XpsN protein forms a stable complex with the XpsD protein. In addition, immune precipitation analysis of the XpsN protein with various truncated XpsD proteins revealed that the C-terminal region of the XpsD protein between residues 650 and 759 was likely to be involved in complex formation between the two.